Estudio de prefactibilidad para el establecimiento de una planta embotelladora de agua tónica - Cornejo Pacheco, José Branco (2019)
This pre-feasibility study aims to verify the viability or non-viability of the installation of a tonic water bottling plant in the Peruvian market in relation with the discount rate of the opportunity cost of capital (17%). In Peru, the market for mixers has been growing strongly, including tonic water. A wide variety of these mixers is consumed in cocktails. However, the vast majority of these are of foreign origin (imported), so the peruvian market of peruvian drinks still has a lot to grow. The volume of demand of mixers was projected with regression techniques to define the target market. Also, with the criteria of geographical and socioeconomic segmentation (metropolitan area, status A and B) and surveys (purchase intention and intensity), it was obtained a prediction of 746.4 hectoliters or 373,200 (200ml) bottles of tonic water for the last year of the project. The factor ranking method was used to establish the plant’s location. Based on various macro and micro-location factors, it was determined that the ideal place for the plant is in the city of Lima, in the district of Lurín. After having chosen the plant’s location, the necessary machines for the production process, the plant’s capacity, the detailed production process, the production program during the 5 years of the project, raw material and input requirements, the number of workers needed, energy requirements and water requirements were determined, as well as the dimensions of each of the areas and the total size of the plant, which is 520 square meters approximately. Finally, the amount of the total investment required for the project was determined, which is 1,239,265 soles. 60% of the total investment will be financed by Corporación Financiera de Desarrollo (COFIDE). After having determined the various budgets (income, costs, expenses), the Statement of Income, the Balance Sheet and the Economic and Financial Cash Flows were made and calculated, with a Rate of Return of 19.3% and 25.3% respectively, higher than the opportunity cost of capital (17%). In conclusion, the installation of a tonic water bottling plant is viable.